A novel LED arrangement to reduce SNR fluctuation for multi-user in visible light communication systems - Zixiong Wang; Wen-De Zhong; Changyuan Yu; Jian Chen (2011 8th International Conference on Information, Communications & Signal Processing, 2011)
The arrangement with 4 LEDs positioned in the corners and 12 LEDs spread evenly on a circle makes the fluctuation of received SNR reduce to 0.85dB. The BER performance does not suffer severely from ISI, where ZF equalization only provides 0.28dB power reduction to achieve BER of 10 -3 when the receiver locates in the corner.